Desain dan Perancangan Internet of Things Sebagai Sistem Kontrol Cerdas Motor 1 Phase - Ihsan, Ihsan; Armin, Armin (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2024)
Developments in the field of technology are growing rapidly and have become one of the necessities of human life. The use of technology that is often used is only general but is not utilized better. The technology in question is planning and designing an intelligent Internet of Things (IoT) system for single-phase induction motors, namely electric machines that run according to the magnetic field induction from the rotor coil. This motor is most widely used by the public, especially in household equipment and some in industry, such as blowers, water pumps and others. In this research, the method that will be used is a prototype design method starting from literature study, model design planning, and an Internet of Things-based control and monitoring system. The results of this research will be in the form of a prototype, design and design of an intelligent control and monitoring system using IoT using Google Assistant. Creating commands on Relays that are associated with feeds on Adafruit IO is done before commands on IFTTT (If This, Then That). If Google Assistant fails to recognize the command made and the information associated with IFTTT, it will respond with a voice that cannot process the command.